Identifying Merdeka Curriculum: An Islamic Teacher’s Perspective in MA Al-Ittihad - Anggarini, Ida Fitri; Amalia, Fanesya Eka (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The curriculum 2013 has been over. The government asks the educator to move from the 2013 curriculum to the Merdeka curriculum. This study aimed to overview the Islamic teacher’s perspective related to the implementation of the Merdeka curriculum on Islamic lessons. The research related to the topic was limited. This qualitative with narrative design study has collected data from four Islamic teachers in MA Al-Ittihad who taught Al Qur’an Hadist, Akidah Akhlak, Fiqh, and Islamic History. The technique for collecting data used observation, semi-structured interviews, and documentation. The study revealed several themes, including the Merdeka curriculum and its implementation, challenges, and alternatives. Also, the Islamic teachers have illustrated the differences between the 2013 and Merdeka curricula in the learning process.